Utilization of Fuzzy Ontology for the Meaning of Homonymous and Homophones Ambiguous Sentences - I Ketut Gede Darma Putra; Risky Aswi Ramadhani (Qubahan Academic Journal)
The ambiguous sentences Homonyms and Homophones become a big problem when processed by computers. From these problems, a Novelty was found; the Novelty created a system that was able to recognize ambiguous sentences of Homonyms and Homophones. The process that the system runs for the first time is to test the proximity of the ambiguous sentences entered with the data set; from this process, the ambiguous sentences entered can already be recognized as the meaning of the sentence. The resulting result is how many per cent the level of similarity. Then the results are processed with the fuzzy ontology method. The results of the Fuzzy Ontology are low similarity level, moderate similarity level, and high similarity level. The method used to analyze this research is the confusion matrix, the precision results obtained were 92%, recall was 100%, and accuracy was 96%. In the future, this research can be used to refine translation results in a translation system.